(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The connection of editorial independence and corporate pressures in this research is considered complex as it pertains to Sustainable Development Goal 16 of dealing with the issues of justice, peace and well-known institutions. An independent/autonomous press is a floor stone of democracy as it is linked and linked with transparency and accountability not to mention publicizing corruption and injustice. However, corporate citizenship forces degrade such a role whereby, due to ownership structure patterns, ads interests and profit motives, independence of such newsrooms and news reporters is curtailed. These pressures normally result in selective reporting or biased reporting or censorship to accommodate the functions of the media as the watchdog of the governance and justice to the disadvantage of the functions of the media as the watchdog of the governance and justice. To critically trace the tension between journalism and corporate dominance, this paper will result in an insight into the threats involved around herding features coupled with the instability of the democratic institutions and voters within the setting wherein the autonomy of the media is to be questioned. It also indicates that the changes of the policy, media standards, and public interest journalism should be considered as the most significant steps to secure SDG 16 and its elements of fairness and strong institutions.